Digital Financial Literacy: A Study of Households of Udaipur - Prasad, Hanuman; Meghwal, Devendra; Dayama, Vijay (Journal of Business and Management, 2018)
Financial literacy has been center of discussion world over. Financial literacy can be generally defined as a person’s ability to understand, analyze, manage, and communicate personal finance matters. More specifically, it refers to the set of skills and knowledge that allows an individual to make informed and effective decisions through their understanding of finances. It is the ability to make informed judgments and take effective decision regarding the use and management of money. Now the trend is change financial literacy become old wine people are moving towards digital financial literacy. The interesting side of digital financial literacy is more people are going of digital payments, the value of internet banking, debit card & credit card, mobile banking are going high. Indian Government is also promoting Digital India recently they have launched many schemes like are Pradhan Mantri Jan Dhan Yojna, Jeevan Jyoti Bima Yojna, Suraksha Bima, MUDRA Bank Yojna, BHIM. The Vittiya Saksharta Abhiyan (VISAKA) also been launched by Ministry of Human Resource. The prime objective of the research is to know the digital financial literacy among the households of Udaipur city. The awareness about various digital platforms and their frequency of use is taken as digital financial literacy. The study further aims to diagnose the impact of personal characteristics on digital financial literacy. The sample of the study is taken from Udaipur city of Rajasthan state of India. A sample of 268 households was selected randomly. A well-structured questionnaire was used to survey and generate digital financial literacy data. The results of study will be a useful direction for both digital platform providers and government to promote citizen for digital transactions. The study also suggests that a wave of awareness campaign is required for bringing more people in the umbrella of digital transaction. Further, a cash transaction oriented economy like India needs to have dual edged sword, where in one hand it needs to bring more policies for lesser use of cash and on the other greater use of digital cash.